The current treatment patterns of metastatic renal cell carcinoma: A national cancer database review, 2004–2015. (July 2019) - Davaro, Facundo; Schaefer, Jared; May, Allison; Raza, Syed Johar; Siddiqui, Sameer; Hamilton, Zachary
Objective: Our objective was to analyze patterns of treatment for metastatic renal cell carcinoma (mRCC) (no treatment (NT), cytoreductive nephrectomy only (CN), systemic therapy only (ST), and both systemic and cytoreductive (ST+CN)), and correlate them with racial or socioeconomic factors. Materials and Methods: Cases of mRCC from 2004–2015 were selected from the National Cancer Database. Our primary outcome was the temporal trend of treatment types. Secondary outcomes included the association of treatment with racial and socioeconomic factors. Logistical regression was performed. Results: In total, 40, 372 patients with mRCC were identified. Treatment modalities included 37.0% NT, 13.9% CN only, 31.6% ST only and 17.5% ST+CN. From 2004–2015, NT decreased (53.4 vs. 32.1%, p < 0.001), CN alone decreased (18.1 vs. 12.1%, p < 0.001), ST alone increased (18.1 vs. 36.7%, p < 0.001) and ST+CN increased (10.3 vs. 19.1%, p < 0.001). On logistical regression, we found non-white races (odds ratio 1.29–1.73, p < 0.001), low-volume centers (hazard ratio (HR) 1.18, p < 0.001), no insurance (HR 2.29, p < 0.001) and low income (HR 1.24, p < 0.001) increased the likelihood of receiving NT. Conclusion: More patients are receiving ST and ST+CN; however, racial and socioeconomic factors may affect the treatment patterns for mRCC, and the underlying cause of these health disparities is unknown. Level of Evidence: 2c6